Stabilisation and the Jamaican commercial banking sector (1991-1997) - Stennett, Robert R. (1999)
Traces the impact of selected macroeconomic variables on the financial sector, with an emphasis on tetermining the relative importance of stabilisatin outcomes in explaining financial sector problems. Notes that the evidence indicates that despite the microeconmic problems in the financial sector, bank distress was also related to macroeconomic factors.